(untitled) (Andamios, Revista de Investigación Social, 2011)
This article elaborates on the cultural and social changes associated with globalization as a large scale mutation. First, I establish a diagnostic about the central features assumed by cultural globalization, following recent debates in the social sciences. Then, I propose a methodological approach on how to read cultural objects, based on their material circulation and their symbolic inscriptions. This perspective builds on the concept of discursive genre as a key to trace the symptoms of changes in the structure of feelings (Williams). Finally the article discusses recent trends in the espionage film genre in order to show thematic, rhetoric and enunciative transformations that indicate an historical rupture associated with globalization processes.